Novel Carboxylated Chitosan-Based Triptolide Conjugate for the Treatment of Rheumatoid Arthritis - Lan Zhang; Min Yan; Kun Chen; Qikang Tian; Junying Song; Zijuan Zhang; Zhishen Xie; Yong Yuan; Yaquan Jia; Xin Zhu; Zhenqiang Zhang; Xiangxiang Wu; et al. (MDPI AG, 2020)
A new platform for triptolide (TP) delivery was prepared by conjugating TP to a carboxylmethyl chitosan (CMCS). Compared with the natural TP, the TP-conjugate (TP-CMCS) containing TP of ~5 wt% exhibited excellent aqueous solubility (> 5 mg/mL). Results of in vitro experiments showed that TP-CMCS could relieve TP-induced inhibition on RAW264.7 cells and apoptosis, respectively. Compared with the TP group, TP-CMCS could effectively alleviate the toxicity injury of TP and decreased the mortality rate of the mice (p < 0.05). TP-CMCS did not cause much damage to the liver (AST and ALT) and kidney (BUN and CRE) (p < 0.05). After administration, the levels of IL-6, IL-1β, and TNF-α decreased, and the arthritis detumescence percentages increased significantly, and the bony erosion degree was distinctly decreased in the TP-CMCS groups and TP group. Our results suggested that TP-CMCS was a useful carrier for the treatment of RA, which enhanced aqueous solubility of free TP and reduced drug toxicity in vitro and in vivo.